The Relationship of Self Assertiveness in Psychological Security and Emotional Intelligence among a Sample of Middle Adolescence Students in North Jordan - Almomani, Mohammad Ali; Al-Khatib, Faryal Youssef; Al-Bashaira, Mahmoud Ibrahim (Journal of Educational and Psychological Sciences, 2021)
The present study aimed at revealing the relationship of self-assertiveness in psychological security and emotional intelligence among a sample of middle adolescence students in north Jordan. The study sample consisted of (1672) male and female students, to achieve the objectives of the study. The results of the study showed that the members of the study sample obtained a medium degree of self-assertiveness and psychological security, and emotional intelligence. The results showed that there was a statistically significant relationship between self-assertiveness and psychological security, and emotional intelligence.
Keywords: Self Assertiveness; Psychological Security; Emotional Intelligence